19F spectroscopy and implications for astrophysics. (October 2020) - La Cognata, M.; Fisichella, M.; Di Pietro, A.; Figuera, P.; Goldberg, V. Z.; Cherubini, S.; Fernandez Garcia, J. P.; Gulino, M.; Lamia, L.; Lattuada, D.; Lattuada, M.; Pizzone, R.G.; et al.
Abstract: The spectroscopy of F is of interest for nuclear astrophysics and nuclear structure. In these proceedings we will focus on the astrophysical implications and on the perspectives of the use of elastic scattering for the investigation of reactions of astrophysical importance. In astrophysics, fluorine and the reactions producing and destroying it play a key role in constraining models of stars in different evolutionary stages, such as the asymptotic giant branch (AGB) stars, responsible of the production of about half of the elements heavier than Fe. Indeed, s-nuclei are produced and brought to the surface thanks to mixing phenomena, together with fluorine that is produced in the same region from the same neutron source. Since the last stage in fluorine nucleosynthesis is the N(α, γ) F radiative capture, the study of the N + α elastic scattering may cast light on the fluorine synthesis. Also, F states are responsible of the appearance of resonances in the O(p, α) N reaction, leading to the production of N, later burnt to F in AGB stars through α-captures. Finally, the F spectroscopy may help constraining nuclear properties of the radioactive mirror nucleus Ne, whose states play a key role in novae modeling through the F(p, α) O reaction. In this work, the N - α elastic scattering is studied using the thick target inverse kinematics approach, allowing us to span a very large fluorine excitation energy range (∼ 6 - 10 MeV). A R-matrix analysis of the measured differential cross sections was also carried out, making it possible to determine the spin-parity and widths of a number of F states, including some previously not reported in the literature.